Modulation of immune mechanisms during hepatoprotective effects of Dawa-Ul-Kurkum, a Unani polyherbal preparation in experimental model of paracetamol induced liver damage in rats - Rafi, Reshi Mohd; Kavita, Gulati; Arunabha, Ray (Asian Journal of Pharmaceutical Research and Development, 2021)
Objective: Iimmunomodulatory effects of Dawa-Ul-Kurkum, a Unani polyherbal preparation and the possible mechanisms in experimental model of paracetamol induced liver damage in rats. Materials and methods: The drug Dawa-Ul- Kurkum has been prepared and provided by CRIUM, Hyderabad. Silymarin was purchased from Sigma-Aldrich (USA) and paracetamol (marketed by Cipla LTD) purchased from general pharmacy shop. Biochemical kits were purchased from ERBA Diagonostic Mannheim Gmbh. Serum alanine aminotransferase (ALT), serum aspartate aminotransferase (AST) and serum alkaline phosphatase (ALP) were estimated by Kinetic method of International Federation of Clinical Chemistry (IFCC), serum bilirubin and total protein were estimated by End Point assay as per the instruction of the Kit Manufacture’s manual.Immunoglobulin and cytokine levels were assessed by ELISA kit manual method. Delayed type hypersensitivity reaction by Institoris et al method. Lipid peroxidation is measured spectrophotometrically as 2-thiobarbituric acid-reactive substance (TBARS), Glutathione (GSH) levels were estimated by the method of Ellman and NOx concentrations were determined by using the Griess reaction as described previously by Tracey et al. Results: Liver damage was induced in Wistar rats by administration of paracetamol and the effects of various drug treatments were assessed on morphological, biochemical, immunoglobulin, cytokine level and histological markers of liver toxicity. In the vehicle treated experimental group, administration of paracetamol induced significant derangements in liver function as evidenced by increased levels of SGOT, SGPT, alkaline phosphatase bilirubin and decrease in total protein, and reductions in body weight and increased liver weights as compared to controls. Histopathological examination showed Periportal necrosis with haemorrhages in experimental control. Pretreatment with Dawa-Ul-Kurkum (DK, 250 and 500 mg/kg) and hydroalcoholic extract of DK (HA, 500 and 1000 mg/kg) showed protective effects against the paracetamol induced biochemical, immunoglobulin, cytokine, delayed type hypersensitivity reaction and histopathological derangements of liver function following paracetamol. Conclusion: Both DK and its 50% hydro-alcoholic extract were found to be effective against paracetamol induced liver damage as they significantly prevented the hepatotoxic damage induced in rats.